Peran Kimia Medisinal dalam Pengembangan Obat Anti Sars Cov-2: Eksplorasi Senyawa Bioaktif dari Teh Hijau (Camellia Sinensis) - Fitya Fithrotun Najiah; Citra Kusumaningsih; Saeful Amin; Hanifiani Kamila (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
COVID-19 is a viral respiratory disease that has caused a global health emergency and was declared a pandemic by the World Health Organization. The lack of certain drug molecules or treatment strategies for this disease is making it worse. Therefore, effective drug molecules are urgently needed to fight COVID-19. Specific therapies for the SARS-COV2 virus are still being developed in several countries around the world. One of the molecular targets that is thought to be specific to SARS-COV 2 is 3CLpro or the main protease of the COVID-19 virus which is an important enzyme to be able to replicate related viruses. The purpose of this study is to explore the role of medicinal chemistry in the development of anti-sars-cov 2 drugs through the exploration of bioactive compounds from natural sources, namely green tea. Green tea (Camellia sinensis) also contains eight native monomeric catechins or polyphenolic compounds. The method used was literature review with analysis of 3 selected articles from international databases such as PubMed, ScienceDirect, and Springer, as well as SINTA accredited national journals. The results showed that all test compounds except caffein had stronger binding energy than lopinavir. Epicatecin and catechin have the same binding energy value as lopinavir, which is -7.1 kcal/mol. Catechin gallate and epicatechin gallate have the strongest bond among all test compounds because they have the most negative AG, namely -9.0 and 8.2 kcal/mol.